2021
DOI: 10.1111/hepr.13693
|View full text |Cite
|
Sign up to set email alerts
|

Early response and safety of atezolizumab plus bevacizumab for unresectable hepatocellular carcinoma in patients who do not meet IMbrave150 eligibility criteria

Abstract: Aim A clinical trial (IMbrave150) indicated the efficacy and safety of atezolizumab plus bevacizumab for patients with unresectable hepatocellular carcinoma (HCC). In this study, we evaluated this therapeutic combination in a real‐world setting, with a focus on patients who did not meet the IMbrave150 eligibility criteria. Methods In this multicenter study, patients with unresectable HCC treated with atezolizumab plus bevacizumab between October 2020 and May 2021 were screened. In patients who did not meet IMb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…They showed good safety and efficacy for these patients. Interestingly, none of the 15 patients with hepatitis B experienced progressive disease [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…They showed good safety and efficacy for these patients. Interestingly, none of the 15 patients with hepatitis B experienced progressive disease [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, appropriate treatment for patients with unresectable HCC who fail to respond to lenvatinib has been an unmet clinical need. Thus, in addition to ICI therapy [ 33 ], TKIs with anti-EGF/EGFR, HGF/c-MET, and/or ANG-2/Tie-2 activity may be a potential therapeutic option. Further analysis is required to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed no significant difference between the pretreatment NLR and the therapeutic response. To understand the other factors associated with the therapeutic response, Sho et al reported that portal vein tumor thrombosis or the hepatitis B virus was significantly associated with PD ( p = 0.039, p = 0.050) [ 17 ]. However, in our study, it was unclear whether PD increased in the case of vascular infiltration because the number of patients with PD was small.…”
Section: Discussionmentioning
confidence: 99%